A trawl survey of seafloor macrolitter on the South African continental shelf. (January 2020) - Ryan, Peter G.; Weideman, Eleanor A.; Perold, Vonica; Durholtz, Deon; Fairweather, Tracey P.
Abstract: Demersal trawls provide an index of seafloor macrolitter abundance, but there are no published data from sub-Saharan Africa. We collected litter items from 235 trawls conducted to assess fish abundance off South Africa. Only 17% of trawls contained litter (3.4 items·km − 2, 2.1 kg·km − 2 but only 0.2 kg·km − 2 excluding four megalitter items). Plastic items predominated (88%), of which 77% floated once cleaned of epibionts. One LDPE bag manufactured three months before being caught carried pelagic goose barnacles Lepas anserifera, confirming that biofouling leads to rapid sinking of floating plastics. Fishery/shipping wastes comprised 22% of litter items (98% by mass; 73% excluding megalitter items); the remainder was general waste – mostly packaging or other single-use items – that could come from land- or ship-based sources. Litter was more abundant in deep water close to Cape Town. The annual demersal trawl survey is a useful way to monitor seafloor litter off South Africa. Highlights: We report the first estimates of seabed litter from trawl surveys off sub-Saharan Africa. Only 17% of trawls contained litter, and densities were low (3.4 items·km − 2 ). Most litter was packaging, but marine wastes accounted for most of the mass of litter. Proximity to Cape Town, a major urban litter source, best explained litter distribution Most plastic items floated, and biofouling probably caused these plastic items to sink.